Green synthesis of silver and iron nanoparticles of isolated proanthocyanidin: its characterization, antioxidant, antimicrobial, and cytotoxic activities against COLO320DM and HT29 - Shejawal, Kiran P. (J Genet Eng Biotechnol, 2020)
BACKGROUND: In the current research, we have developed silver and iron nanoparticles of isolated proanthocynidin (PAC) from grape seed by green synthesis and evaluated for antimicrobial, antioxidant activity and in vitro cytotoxicity against colon cancer cell lines. RESULTS: One percent solution of isolated proanthocynidin in water was vigorously mixed with 1% silver nitrate and 1% ferric chloride solution and kept for 4 h, to yield PACAgNP and PACFeNP. The synthesized nanoparticles were characterized by UV, FTIR, XRD, and SEM analysis and evaluated for antimicrobial potential against selected microbes. Moreover, the synthesized nanoparticles were studied for DPPH assay and in vitro cytotoxicity using colon cancer cell lines COLO320DM and HT29 (MTT, SRB, and Trypan blue assay). UV spectroscopy confirmed the development of nanoparticles. SEM analysis showed that the particles were aggregated in the size range of 50 to 100 nm. Antimicrobial potential was found to be less against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli, whereas cytotoxicity of PACAgNP and PACFeNP against COLO320DM and HT29 exhibited promising results as compared to the pure PAC. PACAgNP and PACFeNP exhibited 20.83 ± 0.33% and 18.06 ± 0.60% inhibition, respectively, against DPPH radical, whereas pure PAC showed 16.79 ± 0.32% inhibition and standard (ascorbic acid) exhibited 98.73 ± 0.18% inhibition of DPPH radical. CONCLUSION: The silver and iron nanoparticles were successfully developed by green synthesis method using isolated proanthocynidin which is economical and eco-friendly. The use of metal nanoparticles may open up a new opportunity for anticancer therapies to minimize the toxic effects of available anticancer drugs specifically in targeting specific site. GRAPHICAL ABSTRACT: [Image: see text]